Long Non-Coding RNAs Involved in Immune Responses - Imamura, Katsutoshi; Akimitsu, Nobuyoshi (Frontiers in Immunology, 2014)
A large number of human RNA transcripts which do not encode proteins are defined as non-coding RNAs (ncRNAs). These ncRNAs are divided into two classes of different lengths; short and long ncRNAs. MicroRNAs are a major class of short ncRNAs, ~22 nucleotides in length that regulate gene expression at the post-transcriptional level. Long non-coding RNAs (lncRNAs) are more than 200 nucleotides in length and play roles in various biological pathways. In this review, we summarize the functions of lncRNAs which regulate immune responses.